Some physico-mechanical properties of composite biomaterials on the basis of biogenic hydroxyapatite with magnetic additives - Otychenko, O.M.; Babutina, T.Ye.; Ziatkevich, D.P.; Bezimyanniy, Yu.G.; Kolesnykov, A.M.; Budylina, O.M.; Protsenko, L.S.; Koval, O.Yu.; Uvarova, I.V. (Functional Materials, 2018)
The effect of ferromagnetic additives in the form of magnetite on composite systems based on biogenic hydroxyapatite (BHA) and obtained by physico-mechanical and chemical methods was studied. It was established that the specific density of BHA/Fe₃O₄ powder obtained by physico-mechanical method for introduction of magnetite is close to that of trabecular bone. Herewith, the density of heat-treated pressed samples from this biomaterial is almost equal to that of cortical bone. Experiments in vitro revealed that a decrease in the material bioresorption is bound with a gradual increase in the amount of Ca²⁺ in the filtrates accompanied by a sharp decrease in PO₄⁻³, Fe²⁺ and Fe³⁺ amounts within 5-7 days. The characteristics of elasticity were established to depend on the porosity and chemical composition of samples, decreasing with introduction of ferromagnetic additives that is probably due to the release of thermally induced carbon dioxide while decompositioning of iron oxalates. The results of this study indicate the expediency of using BHA-based biomaterials in orthopedic practice for restoration of bone tissue functions.